Acorn production is linked to secondary growth but not to declining carbohydrate concentrations in current-year shoots of two oak species - Alla, Arben Q.; Camarero, J. Julio; Maestro-Martínez, Melchor; Montserrat-Martí, Gabriel (Trees, 2011)
In trees, reproduction constitutes an important resource investment which may compete with growth for resources. However, detailed analyses on how growth and fruit production interact at the shoot level are scarce. Primary canopy growth depends on the development of current-year shoots and their secondary growth might also inﬂuence the number and size of fruits supported by them. We hypothesise that an enhanced thickening of currentyear shoots is linked positively to acorn production in oaks. We analysed the effect of acorn production on shoot growth of two co-occurring Mediterranean oak species with contrasting leaf habit (Quercus ilex, Quercus faginea). Length and cross-sectional area of current-year shoots, apical bud mass, number of leaves and acorns, xylem and conductive area, number of vessels of acorn-bearing and non-bearing shoots were measured in summer and autumn. Nitrogen and carbohydrates analyses were also performed in stems and leaves of both shoot types. Stem cross-sectional area increased in acorn-bearing shoots when compared with non-bearing shoots for both species and such surplus secondary growth was observed since summer. In bearing shoots, the total transversal area occupied by vessels decreased signiﬁcantly from basal to apical positions along the stem as did the xylem area and the number of vessels. Leaves of bearing shoots showed lower nitrogen concentration than those of non-bearing shoots. Carbohydrate concentrations did not differ in stems and leaves as a function of the presence of acorns. Such results suggest that carbohydrates may preferentially be allocated towards reproductive shoots, possibly through enhanced secondary growth, satisfying all their carbon demands for growth and reproduction. Our ﬁndings indicate that acorn production in the two studied oaks depends on shoot secondary growth.
Keywords: acorns; Mediterranean climate; nitrogen; non-structural carbohydrates; Quercus faginea; quercus ilex subsp. ballota; Stem diameter; Xylem

Nickel sorption capacity of ground xylem of Quercus ilex trees and effects of selected ligands present in the xylem sap. - Araújo, Geórgia C L; Lemos, Sherlan G; Nabais, Cristina (Journal of plant physiology, 2009)
In this work the influence of four different ligands present in the xylem sap of Quercus ilex (histidine, citric, oxalic and aspartic acids) on Ni(II) adsorption by xylem was investigated. Grinded xylem was trapped in acrylic columns and solutions of Ni(II), in the absence and presence of the four ligands prepared in KNO(3) 0.1molL(-1) at pH 5.5, were percolated through the column. Aliquots of solutions were recovered in the column end for Ni determination by graphite furnace atomic absorption spectrometry (GFAAS). The experimental data to describe Ni sorption by xylem in both the presence and absence of ligands was better explained by the Freundlich isotherm model. The decreasing affinity order of ligands for Ni was: oxalic acid>citric acid>histidine>aspartic acid. On the other hand, the Ni(II) adsorption by xylem increased following the inverse sequence of ligands. Potentiometric titrations of acidic groups were carried out to elucidate the sorption site groups available in Q. ilex xylem. The potentiometric titration has shown three sorption sites: pK(a) 2.6 (57.7% of the sorption sites), related to monobasic aliphatic carboxylic acids or nitrogen aromatic bases, pK(a) 8.1 (9.6%) and pK(a) 9.9 (32.7%), related to phenolic groups.
Keywords: Adsorption isotherms; Nickel; Organic ligands; Xylem

Nickel sorption capacity of ground xylem of Quercus ilex trees and effects of selected ligands present in the xylem sap. - Araújo, Geórgia C. L.; Lemos, Sherlan G.; Nabais, Cristina (Journal of plant physiology, 2009)
In this work the influence of four different ligands present in the xylem sap of Quercus ilex (histidine, citric, oxalic and aspartic acids) on Ni(II) adsorption by xylem was investigated. Grinded xylem was trapped in acrylic columns and solutions of Ni(II), in the absence and presence of the four ligands prepared in KNO(3) 0.1molL(-1) at pH 5.5, were percolated through the column. Aliquots of solutions were recovered in the column end for Ni determination by graphite furnace atomic absorption spectrometry (GFAAS). The experimental data to describe Ni sorption by xylem in both the presence and absence of ligands was better explained by the Freundlich isotherm model. The decreasing affinity order of ligands for Ni was: oxalic acid>citric acid>histidine>aspartic acid. On the other hand, the Ni(II) adsorption by xylem increased following the inverse sequence of ligands. Potentiometric titrations of acidic groups were carried out to elucidate the sorption site groups available in Q. ilex xylem. The potentiometric titration has shown three sorption sites: pK(a) 2.6 (57.7% of the sorption sites), related to monobasic aliphatic carboxylic acids or nitrogen aromatic bases, pK(a) 8.1 (9.6%) and pK(a) 9.9 (32.7%), related to phenolic groups.
The following values have no corresponding Zotero field: accession-num: 18707798
Keywords: Adsorption isotherms; Nickel; Organic ligands; Xylem

Effects of a severe drought on Quercus ilex radial growth and xylem anatomy - Gil-Pelegrín, Eustaquio; Corcuera, Leyre; Camarero, Jesús Julio (Trees - Structure and Function, 2004)
We assessed the response of Quercus ilex subsp. ballota to the severe summer drought recorded in 1994 in NE Spain through the study of changes in radial growth and wood anatomy. We selected a coppice stand in the Iberian Peninsula, which is characterized by a Mediterranean climate under continental influence. We measured internode length, tree-ring width, mean and maximum vessel diameter, and vessel density for 1981– 1997. The annual predicted hydraulic conductance (Kh) was calculated following Hagen-Poisseuille’s law. We compared the tree-ring width, vessel diameter and Kh of Q. ilex subsp. ballota and co-existing ring-porous oaks (Q. faginea, Q. pyrenaica) for a dry summer (1994) and a wet summer (1997). To evaluate the drought-resistance of xylem for Q. ilex subsp. ballota (dominant under continental conditions) and Q. ilex subsp. ilex (dominant in mild areas) we determined vulnerability curves. Dimensionless indices of internode length, tree-ring width, and vessel density were compared with climatic data (monthly total precipitation and mean temperature) using correlation analyses. Internode length, tree-ring width, Kh, and mean and maximum vessel diameter declined in 1994. According to vulnerability curves, Q. ilex subsp. ballota showed a greater drought resistance than Q. ilex subsp. ilex. During the year of growth, we found a positive influence of January and June–August precipitation on the internode length, tree-ring width, and vessel density. The response of Q. ilex subsp. ballota radial-growth to summer drought was comparable to that of Q. faginea latewood. Overall, growth and wood anatomy of Q. ilex subsp. ballota showed a plastic response to drought.
Keywords: cavitation; climate; Dendroecology; vulnerability curve; Xylem

Hydrogen Peroxide Production is a General Property of the Lignifying Xylem from Vascular Plants - BARCELÓ, A R O S (Annals of Botany, 1998)
Production of hydrogen peroxide (H2O2) by the lignifying xylem of several vascular plants has been studied using a new histochemical method based on the H2O2-dependent oxidation of 3,5,3′5′-tetramethylbenzidine (TMB) catalysed by cell wall peroxidases. This method allows H2O2to be determined in the range of 5–100 μm, where other methods, such as the KI/starch reagent, fail. With this method, it has been possible to determine H2O2production in the lignifying xylem of a wide range of vascular plants (gymnosperms and angiosperms). The capability of xylem tissues of sustaining H2O2production lends support to the hypothesis that cinnamyl alcohol polymerization in xylem vessels is caused by an H2O2-dependent oxidative coupling process.Copyright 1998 Annals of Botany Company
10.1006/anbo.1998.0655
Keywords: H2O2 generation; lignification; peroxidase; tetramethylbenzidine; Xylem

Hydrogen Peroxide Production is a General Property of the Lignifying Xylem from Vascular Plants - BARCELÓ, A. R. O. S. (Annals of Botany, 1998)
Production of hydrogen peroxide (H2O2) by the lignifying xylem of several vascular plants has been studied using a new histochemical method based on the H2O2-dependent oxidation of 3,5,3′5′-tetramethylbenzidine (TMB) catalysed by cell wall peroxidases. This method allows H2O2to be determined in the range of 5–100 μm, where other methods, such as the KI/starch reagent, fail. With this method, it has been possible to determine H2O2production in the lignifying xylem of a wide range of vascular plants (gymnosperms and angiosperms). The capability of xylem tissues of sustaining H2O2production lends support to the hypothesis that cinnamyl alcohol polymerization in xylem vessels is caused by an H2O2-dependent oxidative coupling process.Copyright 1998 Annals of Botany Company
10.1006/anbo.1998.065510.1006/anbo.1998.0655
Keywords: H2O2 generation; lignification; peroxidase; tetramethylbenzidine; Xylem